2D versus 3D Endoscopy: Head-to-Head Comparison in a Simulated Model of Endoscopic Endonasal Dural Suturing - Nebor, Ivanna; Anderson, Zoe; Mejia-Munne, Juan C.; Hussein, Ahmed; Montemagno, Kora; Fumagalli, Rebecca; Labiad, Ikrame; Patil, Yash; Andaluz, Norberto; Sedaghat, Ahmad R.; Zuccarello, Mario; Forbes, Jonathan A. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Endonasal dural suturing (EDS) has been reported to decrease the incidence of cerebrospinal fluid fistula. This technique requires handling of single-shaft instrumentation in the narrow endonasal corridor. It has been proposed that three-dimensional (3D) endoscopes were associated with improved depth perception. In this study, we sought to perform a comparison of two-dimensional (2D) versus 3D endoscopy by assessing surgical proficiency in a simulated model of EDS.Materials and Methods Twenty-six participants subdivided into groups based on previous endoscopic experience were asked to pass barbed sutures through preset targets with either 2D (Storz Hopkins II) or 3D (Storz TIPCAM) endoscopes on 3D-printed simulation model. Surgical precision and procedural time were measured. All participants completed a Likert scale questionnaire.Results Novice, intermediate, and expert groups took 11.0, 8.7, and 5.7 minutes with 2D endoscopy and 10.9, 9.0, and 7.6 minutes with 3D endoscopy, respectively. The average deviation for novice, intermediate, and expert groups (mm) was 5.5, 4.4, and 4.3 with 2D and 6.6, 4.6, and 3.0 with 3D, respectively. No significant difference in procedural time or accuracy was found in 2D versus 3D endoscopy. 2D endoscopic visualization was preferred by the majority of expert/intermediate participants, while 3D endoscopic visualization by the novice group.Conclusion In this pilot study, there was no statistical difference in procedural time or accuracy when utilizing 2D versus 3D endoscopes. While it is possible that widespread familiarity with 2D endoscopic equipment has biased this study, preliminary analysis suggests that 3D endoscopy offers no definitive advantage over 2D endoscopy in this simulated model of EDS.
Keywords: 2D endoscope; 3D endoscope; dural suturing; 3D model; surgical simulator